Kekuatan Nilai untuk Melestarikan Biosper: Menguji Peranan Orientasi Nilai Terhadap Perilaku Berkelanjutan: The Power of Values in Preserving the Biosphere: Examining the Role of Value Orientation in Sustainable Behavior - Trihapsari, Tunjung; Shadiqi, Muhammad Abdan; Achmad, Rendy Alfiannoor (Mediapsi, 2024)
Various phenomena of environmental degradation require people to act immediately to implement more sustainable behaviors and lifestyles. This study aims to investigate the role of value orientation in sustainable behavior among the Environmental Engineering students of Lambung Mangkurat University. The study method was quantitative, with a total sample of 125 Environmental Engineering students in at least the second year (batch of 2021, 2020, 2019). The subjects were selected using the simple random sampling technique. The measurement instruments included the adapted Sustainable Behavior Scale and the Environmental Portrait Value Questionnaire (EPVQ) scale. The data were analyzed using multiple linear regression. The results of the hypothesis testing show that among the four dimensions of value orientation, only the biospheric dimension played a significant role in sustainable behavior. In contrast, the altruistic, hedonic, and egoistic dimensions did not play a role in sustainable behavior. However, all the value dimensions simultaneously played a role in sustainable behavior. The coefficient of determination shows that the value orientation had a role in sustainable behavior.   Keywords: Sustainable behavior, value orientation, environmental engineering students